2019
DOI: 10.1590/1807-3107bor-2019.vol33.0054
|View full text |Cite
|
Sign up to set email alerts
|

Skin color affect the replacement of amalgam for composite in posterior restorations: a birth-cohort study

Abstract: The aim of present study was to estimate the occurrence and associated factors for replacement of amalgam posterior restorations. A representative sample of all 5,914 births from the 1982 in Pelotas birth cohort study was prospectively investigated, and the posterior restorations were assessed at 24 (n = 720) and 31 years of age (n = 539). Individual-level variables, i.e., demographic characteristics, socioeconomic factors, oral health conditions and use of dental services, were collected from different waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
16
0
2
Order By: Relevance
“…Thus, unequal relationships between social groups shape their distribution to adverse exposures and health conditions. Discrimination in oral health services in Brazil has been highlighted in a recent study 32 and racism has also affected the dentists' decision concerning the replacement of amalgam restorations 33,34 , emphasizing the structural racism that stereotypes and stigmatizes these populations 10 . In this way, it is important to deeply discuss the social-historical roots of Brazilian racism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, unequal relationships between social groups shape their distribution to adverse exposures and health conditions. Discrimination in oral health services in Brazil has been highlighted in a recent study 32 and racism has also affected the dentists' decision concerning the replacement of amalgam restorations 33,34 , emphasizing the structural racism that stereotypes and stigmatizes these populations 10 . In this way, it is important to deeply discuss the social-historical roots of Brazilian racism.…”
Section: Discussionmentioning
confidence: 99%
“…tists, similar to Brazil, which present around 20% of all the world's dentists and a competitive labor market 39 . Moreover, dentist's treatment decision-making is not only influenced by the patients' oral condition, being influenced by cost of treatments and patients characteristics, such as skin color and economic status 40,41,42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the complete understanding of mechanisms that professional decision making is a hard task and can englobe several levels of comprehension, beginning in the professional knowledge 17,24 , influenced by the school of dentistry and, also, can be influenced by patients' characteristics [25][26][27] . Some patient's characteristics could influence the decision making of health professionals [25][26][27] . Moreover, it was observed that competition affected the clinical decision-making of dentists in Canada 28 .…”
Section: Discussionmentioning
confidence: 99%